Measurement of CP violation in the B s 0 → ϕϕ $$ B_s^0→ φ φ $$ decay and search for the B 0 → ϕϕ decay - The LHCb collaboration; R. Aaij; C. Abellán Beteta; B. Adeva; M. Adinolfi; C. A. Aidala; Z. Ajaltouni; S. Akar; P. Albicocco; J. Albrecht; F. Alessio; M. Alexander; et al. (Journal of High Energy Physics, 2019)
Abstract A measurement of the time-dependent CP-violating asymmetry in B s 0 → ϕϕ $$ B_s^0→ φ φ $$ decays is presented. Using a sample of proton-proton collision data corresponding to an integrated luminosity of 5.0 fb −1 collected by the LHCb experiment at centre-of-mass energies s $$ \sqrt{s} $$ = 7 TeV in 2011, 8 TeV in 2012 and 13 TeV in 2015 and 2016, a signal yield of around 9000 B s 0 → ϕϕ $$ B_s^0→ φ φ $$ decays is obtained. The CP-violating phase ϕ s s s ¯ s $$ φ_s^{s\overline{s}s} $$ is measured to be −0.073 ± 0.115(stat) ± 0.027(syst) rad, under the assumption it is independent of the helicity of the ϕϕ decay. In addition, the CP-violating phases of the transverse polarisations under the assumption of CP conservation of the longitudinal phase are measured. The helicity-independent direct CP-violation parameter is also measured, and is found to be |λ| = 0.99 ± 0.05(stat) ± 0.01(syst). In addition, T-odd triple-product asymmetries are measured. The results obtained are consistent with the hypothesis of CP conservation in b ¯ → s ¯ s s ¯ s $$ \overline{b}→ \overline{s}s\overline{s}s $$ transitions. Finally, a limit on the branching fraction of the B 0 → ϕϕ decay is determined to be B B 0 → ϕϕ < 2.7 × 10 − 8 $$ \mathcal{B}\left(B^0→ φ φ \right)<2.7× {10}^{-8} $$ at 90 % confidence level.